RANCANG BANGUN POMPA HIDRAM UNTUK MENGATASI KETERBATASAN SUMBER ENERGI LISTRIK - Tauvana, Ade Irvan; Widodo, Widodo; Nulhakim, Lukman; Anugrah, Hari (Jurnal Teknologi Terapan, 2025)
Puteran Village, Cikalong Wetan District, West Bandung Regency is the one that needs a hydram pump to utilize the spring water in Puteran Village to meet daily needs. This hydram pump is a pump that utilizes the power of water flowing from a source and some of the water is pumped to a higher place. This pump does not use electrical energy, so it can be used in areas where electricity is difficult or limited. This research includes design and assembly, this pump uses PVC pipe measuring ½", 2", 3" and 4". Tests were carried out by varying the diameter and length of the hydram pump tube. Water flows from the spring to the hydram pump at a distance of 6 meters with a height of 1 meter, while the distance from the pump to the water reservoir is 60 meters with a height of 2 meters. The total cost of making a hydram pump is Rp. 822,000,- and the largest variation in the 4" diameter air tube with a height of 1 meter produces a water discharge of 0.0000668 m3/s with a D' Aubuisson hydram pump efficiency of 82.59% and a Rankine hydram pump efficiency of 63.85%.